The Entrepreneurial Ability and Success for the Entrepreneurship - Lydeka, Zigmas (Ekonomika, 2000)
Tile objective as much as subjective reasons decide that business people become the decisive subjects of the economic development. The business person, as the active subject of the economic development, surpasses the economic reality by his thought activity. The new reasoning and knowledge is oriented not as much to activity intensification as to the change of structure and means of activity. This stipulation forms a principally new altitude towards the current and future entrepreneurship in which the criteria for the evaluation of the economic activity change (in other words. the only evaluation criterion-moneyis rejected). In the activity of business people, new evaluation criteria appear: intellectual, psychological, cultural, ecological, etc. The entrepreneurial ability expresses the inner professional- personal potential of a business person. This potential is indispensible in order to start a new business. The entrepreneurial ability is the innate or acquired personal qualities that allow an individual to reason innovatively and act at risk. Entrepreneurial ability does not only involve the wish to act. It also involves the ability and skill to reason innovatively and to act at risk in diverse situations of economic life. The enterpreneurial ability means the skill of being able to use the internal potential and favour of the situation for creating profit (increase of property). During the period of transformation, when the prerequisites necessary for functioning of the market economy are deficient, there is an obvious disproportion between the innate and acquired entrepreneurial qualities. As the economic system of the market economy becomes more developed, the innate qualities (knowledge and practical experience that helps people find unique meanings in unique situations and make independent authentic decisions) should become more important. After the economic system of market has been fully formed, the innate and acquired qualities should combine with each other at a certain ratio that will be determined by the processes of formation of prerequisites for the new economic system. The strive for success of enterpreneurial ability can be characterised as the process of managing the discrepancy between the unlimited wishes (aspirations) and limited possibilities (abilities). The essential prerequisites for strive of success are unlimited wishes (W), limited possibilities (P), the discrepancy between the unlimited wishes and limited possibilities (DWP). The process of strive for success, as optimization of the discrepancy between the unlimited wishes (W) and limited possibilities (P), might be understood by limit phenomena and, therefore, limit measures should serve as criteria of their managing (the general maximization of the rate of success).